The guanylate binding protein-1 GTPase controls the invasive and angiogenic capability of endothelial cells through inhibition of MMP-1 expression - Naschberger, Elisabeth; Stürzl, Michael; et al. (EMBO Journal, 2003)
Expression of the large GTPase guanylate binding protein-1 (GBP-1) is induced by inflammatory cytokines (ICs) in endothelial cells (ECs), and the helical domain of the molecule mediates the repression of EC proliferation by ICs. Here we show that the expression of GBP-1 and of the matrix metalloproteinase-1 (MMP-1) are inversely related in vitro and in vivo, and that GBP-1 selectively inhibits the expression of MMP-1 in ECs, but not the expression of other proteases. The GTPase activity of GBP-1 was necessary for this effect, which inhibited invasiveness and tube-forming capability of ECs in three-dimensional collagen-I matrices. A GTPase-deficient mutant (D184N-GBP-1) operated as a transdominant inhibitor of wild-type GBP-1 and rescued MMP-1 expression in the presence of ICs. Expression of D184N-GBP-1, as well as paracrine supplementation of MMP-1, restored the tube-forming capability of ECs in the presence of wild-type GBP-1. The latter finding indicated that the inhibition of capillary formation is specifically due to the repression of MMP-1 expression by GBP-1, and is not affected by the anti-proliferative activity of the helical domain of GBP-1. These findings substantiate the role of GBP-1 as a major regulator of the anti-angiogenic response of ECs to ICs.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Collagenase; Inflammation; Invasion; MMP